Lietuviška knyga carinės cenzūros brūzgynuose (XIX amžiaus pirmoji pusė) - Medišauskienė, Zita (Knygotyra, 1998)
The present article is based on archival and historiographical data and represents a discussion about the censorship of Lithuanian books in 1804–1865.A systematic secular preventive censorship of Lithuanian books was started at the beginning of the 19th century when in 1804 a Committee of Censorship was established at the Vilnius University. The university professors were elected as censors. In their examination of books they followed the law of censorship and instructions of the minister of education. In Lithuanian and Polish books it was forbidden to publish any antistate, revolutionary and godless ideas. A special attention was paid to the literary or scientific value of books and „moral aspirations” expressed in them. It was recommended to devote to commons only religious and didactic works.After 1826 a political emphasis in censorship strengthened. Gradually the criteria of scientific or literary value were repudiated. Notwithstanding all this till 1851 the Lithuanian books, mostly represented by religious works, were censored rather loosely following only the general regulations of censorship in the Russian Empire. Actually, there were no repressions on the part of censorship.In 1851 the situation changed. Taking into consideration the experience of European revolutions of 1848 the Russian government revised its policy with regard to Lithuanians and took measures (including the censorship) to more efficiently control the spiritual and cultural life of Lithuanians. Since then censors followed not only the general regulations of censorship and special requirements for commons books (this category included the Lithuanian books) but also special instructions incited by the principles of Russian policy towards Lithuania.It was strictly required that the Lithuanian books were loyal to Russia, favourably disposed towards Russians, unconditionally respectful to emperor's rule and person, respectful to all civil officers and institutions of government in general. Social problems were forbidden, i. e., social criticism and social pessimism, pictures of oppression and poverty were not tolerated. The political aspirations of Russian government in Lithuania affected mostly the censorship of religious and historical texts. Safeguarding the respect for any christian religion the Russian censorship tried at the same time to belittle the influence of Catholic Church on Lithuanian people. For this reason all propositions about the superiority of religious power against the secular one, pope as the head of Catholic Church, etc., were eliminated. The propagation of church fraternities was prevented (especially the fraternity of soberness). The censorship prohibited any manifestations of religious intolerance, especially the one directed against orthodox believers. From the Lithuanian religious writing all dogmata distinguishing the Catholic belief from other christian religions were eliminated. In this way the Russian government attempted to create better preconditions for dissemination of orthodox religion. It was also the duty of censors to prevent Lithuanian peasants from taking over from nobility the tradition of self-dependent Lithuanian state. For this reason, notwithstanding that it was allowed to publish some historical facts they had to be described without emotions and praising of the Grand Duchy of Lithuania; especially when the facts did not conform with the official Russian historiography.Therefore, the censorship had not only to help maintain the existing political and social structure but also to abolish in Lithuania those religious and historical factors which emphasized the difference between Lithuanians catholics and Russians – orthodox believers. The erasure of these differences was one of the main preconditions of Lithuania's integration into Russian Empire.